PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM (Studi pada Perusahaan Perbankan di Bursa Efek Jakarta) - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2005)
ABSTRACT Make-Up of Loan to Deposit Ratio have an effect on to degradation of share price. Excelsior Loan to Deposit Ratio give indication progressively lower nya ability of pertinent bank likuiditas which cause to degradation of share price. Make-Up of Capital Ratio have an effect on to make-up of share price, with make-up of Capital Ratio give bank capital information enough support bank operation and can permeate loss of bank in conducting fund cultivation causing also the make-up of share price. high Return On Equity express ability of bank yield high advantage to stockholder causing request of share mount hereinafter will have an effect on the increasing of share price. Dividend Per Share do not have an effect on to share price change. This matter is caused by many company of banking which do not pay for dividend during period 2002 - 2003, change of Debt to Equity don't have influence to share price change, its logic is ever greater of DER hence will be ever greater of accounted by risk is investor. Keywords: definition stres, symptom stress, management stres, change,